Predictive Role of Cognitive Distortions and Motivation Regulation on Math Anxiety among Turkish High School Students - ÜMMET, DURMUŞ (My University, 2023)
The aim of this study is to examine mathematics anxiety in high school students according to cognitive distortions and motivation regulation variables related to academic anxiety. The sample of the study consists of a total of 436 students (283 girls and 153 boys) studying at different high schools in Turkey in the 9th, 10th, 11th and 12th grades. Mathematics Anxiety Scale (MAS), Cognitive Distortions Scale Related to Academic Achievement (CDS-AA) and Motivation Regulation Scale-Short Form (MRS-SF) were used to collect the data of the research. According to the findings obtained; a significant negative correlation was found between high school students' math anxiety and motivation regulation skills. In addition, it was determined that there were positive significant relationships between students' math anxiety and both the total scores of cognitive distortions related to academic achievement and the subdimension scores of catastrophizing, perfectionism, self-value, and outer attribution. According to the results of the regression analysis, it was determined that motivation regulation and cognitive distortions scores were a significant predictor of students' math anxiety. The findings were discussed with other studies in the field and some suggestions were made.
Keywords: Math anxiety; motivation regulation; cognitive distortions; high school students